Effect of Fly Ash on Mortar Mixes with Quarry Dust as Fine Aggregate - Baboo Rai; Sanjay Kumar; Kumar Satish (Advances in Materials Science and Engineering)
This paper presents the results of an experimental investigation carried out to evaluate the compressive strength and transverse strength of 1 : 3 mortar mixes in which natural sand was replaced with 20%, 50%, and 100% quarry dust by weight which were further modified by partially replacing cement with four percentages (15%, 20%, 25%, and 30%) of low calcium fly ash. The compressive strength was determined at 3, 7, 28, and 50 days of age while transverse strength was determined at 28 and 50 days age. Test results revealed that the combined use of quarry rock dust and fly ash exhibited excellent performance due to efficient microfilling ability and pozzolanic activity.